Circular Economy and Its Impact on Economic, Environment and Societal Aspects: A Survey Among Fashion Industry Business in Lalitpur, Nepal - Shrestha, Richan; Shakya, Rushma; Shrestha, Akita (Apex Journal of Business and Management, 2025)
Despite the global shift towards sustainability, the adoption of Circular Economy (CE) principles within the Nepalese fashion industry remains understudied. This research aims to fill this gap by exploring the potential benefits and influence of implementing CE practices in this sector on society, environment, and the economy. The primary objective of this study is to investigate the knowledge, attitudes, and practices related to CE among individuals in the fashion industry in Lalitpur, Nepal, and to assess the impact of CE practices on various dimensions. This study employs a quantitative research design utilizing a survey approach grounded in CE principles. Data were collected through a self-administered questionnaire distributed to individuals associated with the fashion industry in Lalitpur, resulting in a sample size of 220 respondents. The findings indicate a moderate level of knowledge, attitude, and practice regarding CE principles among individuals in the fashion industry. Furthermore, there is a positive and significant impact of CE practices on societal, environmental, and economic aspects. This research represents the first instance of such a study in Nepal's fashion sector. The findings are valuable for environmental policymakers, fashion entrepreneurs, educational institutions, and future researchers seeking to enhance sustainability within the industry.